The construction of a unified style: poetry composed by the Kuizhang Academicians in the Early 14th Century - Hui, MTT (School of Humanities at Nanyang Technological University, 2023)
The study of classical literature during the Mongol-Yuan dynasty (1271–1368) is often associated with investigating the cultural activities of literary groups. Fueled by the interest in localism, many scholars are understandably more concerned about the strategies of local literati and the role that classical literature played in fourteenth century local societies. However, among the literary groups that emerged during the Mongol-Yuan, the Kuizhang Academicians stand out as a particular literary circle, since the poets involved were affiliated with the court. This paper examines the works of the Academicians, specifically how they attempted to cultivate a literary style that could represent their generation. The paper first examines Yu Ji’s literary criticism and then explores how his ideas influenced his follower, Su Tianjue. The paper then turns to an examination of the poems recorded in the anthology Guochao wenlei (Categorized Writings of Our Dynasty) and demonstrates how Su, the compiler of this anthology, tended to overlook the differences in styles among the courtiers and instead emphasized a certain type of poetry that could reflect Yu Ji’s vision. Through a close reading of some of the poetic works composed by the Kuizhang Academicians, this paper seeks to unravel the complexities of the aesthetic preferences of the time.